(untitled) (Journal of Pharmaceutical Negative Results, 2022)
AIM: The study aimed at synthesising a novel herbal based, alcohol free mouth rinse, containing green synthesised-selenium nanoparticles and chitosan colloid and assessing its antibacterial properties. MATERIALS AND METHODS: A novel herbal mediated synthesis of selenium nanoparticle synthesis was employed in this study. This study used Stevia leaves for nanoparticle synthesis in combination with Sodium selenite. This mixture was mixed homogeneously using an orbital shaker. Colour change indicated formation of SeNPs. The SeNP’s were characterized for shape and size using TEM (transmission electron microscopy) analyses and UV vis spectrophotometry. A novel mouth rinse containing Selenium nanoparticles and Chitosan colloid as made. The activity against microbes of the mouth rinse was evaluated using agar gel diffusion technique. The inhibition zones were measured for: Enterococcus faecalis, Streptococcus mutans, Staphylococcus aureus and Candida Albicans at 25µL, 50µL ,100µL concentration. RESULTS:Herbal mouth rinse showed excellent antimicrobial activity against S.aureus and C.albicans at all concentrations. Following S. aureus, the mouth rinse was effective against S. mutans at 50 and 100 µL concentration and against Faecalis at 100 µL. CONCLUSION:The herbal alcohol-free mouth rinse consisting of Selenium Nanoparticles and Chitosan colloid is effecient in inhibiting the activity of oral microorganisms and could be used as an adjunct to mechanical methods of plaque removal in orthodontic patients.